An Analysis of Positive Politeness Strategy Used on Expressive Utterance in “The School for Good and Evil” Movie - Atsna, Jazila; Andriyani, Santi (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study investigates the use of positive politeness strategies in the movie The School for Good and Evil, utilizing Brown and Levinson's politeness theory (1987). By analyzing expressive utterances, the research examines how characters convey emotions, maintain relationships, and enhance interpersonal interactions within a fantasy setting. A qualitative descriptive method was employed, with data sourced from the movie and its script. The findings reveal that the characters employ various strategies such as noticing, exaggeration, using in-group identity markers, avoiding disagreements, and offering promises to navigate themes of identity, belonging, and moral dichotomy. These strategies foster solidarity, resolve conflicts, and strengthen social bonds in the fantastical context of the story. However, the study's reliance on a single movie limits the generalizability of the findings, highlighting the need for further research across different genres and cultural contexts. This study contributes to linguistic research by showcasing how positive politeness strategies are adapted in unique narrative settings and provides insights for improving communication in real-world contexts, such as educational environments.